Barefoot vets - a stop-gap measure - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Dr Sultan of FARM-Africa Tanzania discusses a project to train community animal health workers, describing the training system, the benefits the barefoot vets are offering to communities and their relationship with government veterinary services.